Analisis Penerapan Penatausahaan Penerimaan Desa Melalui Sistem Keuangan Desa (SISKEUDES) Berbasis Cash Management System (CMS) Di Kabupaten Sragen - Amelia Indah Agustina; Irsyadul Ibad (JURNAL ADMINISTRASI KANTOR, 2025)
This study aims to examine the implementation of village revenue administration through the Village Financial System (SISKEUDES), which has been integrated with the Cash Management System (CMS) in Sragen Regency. The research employed a qualitative method. Data were collected through interviews, observations, and documentation. The informants in this study consisted of three individuals: the Head of the Division of Village Administration Development and Structuring, the SISKEUDES Section Head, and the SISKEUDES Administrator at the regency level. The results indicate that the implementation of SISKEUDES in Sragen Regency has been carried out in accordance with the standard operating procedures (SOP) for financial management. The use of SISKEUDES has enhanced the transparency and accountability of village financial management. Moreover, it has facilitated the work of village officials, particularly in the recording and reporting of village revenues. The integration of CMS into SISKEUDES allows financial transactions to be synchronized directly and in real time with GIBSBank Jateng, thereby improving administrative efficiency. The Sragen Regency Community and Village Empowerment Office also plays a significant role as a supervisor and mentor in the implementation process, providing guidance to village governments to ensure optimal SISKEUDES performance. Keywords:Information System, Village Financial Management, Cash Management System, Administration, Village Revenue